Degradation of methylene blue and methyl violet using graphene oxide/NiO/β-cyclodextrin nanocomposites as photocatalyst. Issue 17 (23rd December 2022) - Dewangan, Ranjana; Hashmi, Ayesha; Asthana, Anupama; Singh, Ajaya K.; Susan, Md Abu Bin Hasan
ABSTRACT: We report the synthesis of graphene oxide/nickel oxide/β-cyclodextrin (GO/NiO/β-CD) nanocomposite and the efficiency of the nanocomposite in decolourising two different dyes, methylene blue (MB) and methyl violet (MV). GO was prepared by modified Hummer's method while hydrothermal method was used for the preparation of GO/NiO/β-CD. The as-synthesised nanocomposites were characterised by X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy and high resolution transmission electron microscopy (HR-TEM). Photocatalytic degradation was carried out under solar light by monitoring the concentration of MB and MV dyes. Degradation reaction followed Langmuir-Hinshelwood pseudo first-order kinetic model. The apparent reaction rate constant (k) for MB increased as compared to MV under solar light irradiation. The MB showed better photocatalytic degradation efficiency by GO/NiO/β-CD composites. GO/NiO/β-CD nanocomposite has been very favourable for photocatalytic application.